Die beskerming en beperking van regte met betrekking tot godsdiensinstellinge - Landman, CH (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The paper is entitled “the protection and limitation of rights in relation to religious institutions – problems and possibilities”. The author argues that religious associations as organs of civil society should pro-actively formulate and accept internal rules regarding its unique mode of existence, within the context of and in relation to the provisions of the Bill of Rights of the Constitution of SA.